Synthesis of Passerini adducts from aldehydes and isocyanides under the auxiliary of water1. Issue 10 (14th October 2015) - Li, Ming; Qiu, Bin; Kong, Xiang-Jing; Wen, Li-Rong
<x xml:space="preserve">Abstract</x> An efficient protocol for the synthesis of the Passerini adducts α-acyloxycarboxamides from aldehydes, isocyanides and water in a molecular ratio of 3 : 1 : 3 was described.